Nordic walking training in elderly, a randomized clinical trial. Part II: Biomechanical and metabolic adaptations - Gomeñuka, Natalia Andrea (Sports Med Open, 2020)
BACKGROUND: Nordic walking is an attractive method of endurance training. Nevertheless, the biomechanic response due to the additional contribution of using poles in relation to free walking training has been less explored in the elderly. Purpose: This randomized parallel controlled trial aimed to assess the effects of 8 weeks of Nordic walking and free walking training on the walking economy, mechanical work, metabolically optimal speed, and electromyographic activation in elderly. METHODS: Thirty-three sedentary elderly were randomized into Nordic walking (n = 16) and free walking group (n = 17) with equalized loads. Submaximal walking tests were performed from 1 to 5 km h(−1) on the treadmill. RESULTS: Walking economy was improved in both free and Nordic walking groups (x(2) 4.91, p = 0.014) and the metabolically optimal speed was increased by approximately 0.5 km h(−1) changing the speed-cost profile. The electromyographic activation in lower and upper limbs, pendular recovery, and total, external, and internal mechanical work remained unchanged (p > 0.05). Interestingly, the internal mechanical work associated with arm movement was higher in the Nordic walking group than in the free walking group after training, while the co-contraction from upper limb muscles was reduced similarly to both groups. CONCLUSIONS: Eight weeks of Nordic walking training effectively improved the walking economy and functionality as well as maintained the gait mechanics, similar to free walking training in elderly people. This enhancement in the metabolic economy may have been mediated by a reduction in the co-contraction from upper limb muscles. TRIAL REGISTRATION: ClinicalTrails.gov NCT03096964